Angle Displacement Robust Controller for the Port Plate of the Hydraulic Transformer. (12th December 2013) - Shen, Wei; Jiang, Jihai; Su, Xiaoyu; Karimi, Hamid Reza
Abstract : The hydraulic transformer is used in the hydraulic system to enhance the efficiency. However, how to control the angle displacement of the port plate is becoming a critical issue because of the new structure of the hydraulic transformer. This paper presents a new method for the angle displacement control system. Firstly, the basic principle of the system is presented. Then, the disturbance which is mainly the friction torque between the port plate and the cylinder block is calculated to estimate the range. Furthermore, the guaranteed cost control (GCC) is analyzed and combined with the disturbance and the characteristics of parameter uncertainties. Finally, the proposed control method is compared with the traditional PI control and the simulation result shows the effectiveness of the proposed design method.